Effects of exosomes of paratumoral thymus epithelial cells on Treg cell function in patients with thymoma-associated myasthenia gravis - CHEN Liuling; TAN Shuting; BAO Xiaoran; LIU Jingli; LI Jinpin (Guangxi Yike Daxue xuebao)
Objective To investigate the effects of exosomes derived from paratumoral thymic epithelial cells on the expression of forkhead box protein P3 (FOXP3) and the secretion of transforming growth factor-beta1 (TGF-β1) and interleukin (IL)-10 by regulatory T cells (Tregs) in patients with thymoma-associated myasthenia gravis (TAMG). Methods Thymic epithelial cells were isolated and cultured from TAMG patients and patients with congenital heart disease without thymus disease (control group), and identified by immunofluorescence staining with pan-cytokeratin (p-CK) and Vimentin. The exosomes were extracted from thymic epithelial cells by membrane affinity column and identified by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA) and western blotting. Tregs were isolated from thymic epithelial cells by magnetic bead sorting and their purity was detected by flow cytometry. Tregs were co-cultured with exosomes, and exosome staining and tracing experiments were performed to detect the expression of FOXP3 and the levels of TGF-β1 and IL-10 in the culture supernatant. Results The isolated cells were spindle-shaped and grew well. Immunofluorescence showed that the cells were positive for p-CK and negative for Vimentin, and the cells were thymic epitheliallls. TEM, NTA and western blotting results suggested that the extracts were exosomes. The purity of Tregs detected by flow cytometry was more than 90%, with good purity. The results of exosome staining showed that Tregs could phagocytose exosomes from thymic epithelial cells. After co-culture with exosomes of thymus epithelial cells in TAMG group, the expression of FOXP3 in Tregs was decreased (P＜0.01) and the secretion of TGF-β1 and IL-10 was decreased (P＜0.01). Conclusion Tregs can phagocytose exosomes of paratumoral thymic epithelial cells of TAMG, leading to decreased FOXP3 expression, decreased secretion of TGF-β1 and IL-10, and weakened immunosuppressive function, which may be involved in the pathogenesis of TAMG.